Bug or no bug: challenges in diagnosing cutaneous mycobacterial infections. (22nd July 2016) - Peters, Franziska; Batinica, Marina; Plum, Georg; Eming, Sabine A.; Fabri, Mario
Summary: Cutaneous mycobacterioses are rare in Germany. Nevertheless, early diagnosis and subsequent effective treatment requires awareness of these conditions. Moreover, mycobacterial infections are on the differential diagnosis list of many skin diseases. Diagnoses of cutaneous mycobacterioses are based on clinical features, but also on laboratory investigations, including bacterial culture, histopathology and PCR‐based methods. Knowledge about the opportunities and limitations of theses laboratory tests is pivotal to reasonable clinical decision‐making. In this paper, we review the current diagnostic options when suspecting a case of cutaneous mycobacterial infection.